POWER BUDGET ANALYSIS OF REFLECTED GPS L1 AND L5 FREQUENCY SIGNALS FOR PASSIVE MICROWAVE IMAGING - Sakhawat, S.; Usman, M.; Hanif, A. (The Nucleus, 2014)
The GPS signals are commonly used for navigation purposes. Another utilization of reflected GPS signals is for remote sensing. This paper focuses on the power budget analysis of bi-static radar using GPS satellite as a â€œtransmitter of opportunityâ€. In this application the direct and reflected GPS signals are acquired using customized hardware, where the receiver can be mounted on an airborne platform or remain static. GPS satellites currently transmit L1 frequency signals with C/A codes used as a ranging signal, but plans for transmitting additional L5 frequency signals as part of GPS modernization efforts are underway. Here we present the simulated results for power budget analysis of both GPS L1 and L5 frequency signals. The Signal to Noise Ratio (SNR) for different ranges is calculated and results have been plotted. It can be deduced that SNR of GPS L5 reflected signal is higher as compared to GPS L1 signal for similar target ranges and therefore, these signals are more suitable for remote sensing applications as compared to GPS L1 signals. Simulation is carried out in MATLABÂ®.